2018
DOI: 10.1002/chem.201804368
|View full text |Cite
|
Sign up to set email alerts
|

A Dimeric 2,9‐Diamino‐1,10‐phenanthroline Derivative Improves Alternative Splicing in Myotonic Dystrophy Type 1 Cell and Mouse Models

Abstract: Expanded r(CUG) repeatsare the cause of the neurological disorder myotonic dystrophy type1 (DM1). The pathological features of DM1 include the formation of ribonuclearf oci containinge xpanded r(CUG) repeats, whichs equestert he MBNL1 protein and lead to the misregulation of alternative pre-mRNA splicing.S mall molecules that bind to the r(CUG) repeats and improve alternative splicingh ave therapeutic potentiali nt he treatment of DM1. Herein, the synthesis of DDAP (a dimericform of the CUG-binding molecule DA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
31
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(31 citation statements)
references
References 62 publications
0
31
0
Order By: Relevance
“…Some small molecules were also found to act on other types of disease-related RNAs or pathogenic RNA motifs. Many of them are for RNA repeats, such as the expanded GGGGCC repeat [r(GGGGCC) exp , or r(G4C2) exp , or G-quadruplex RNA], which causes frontotemporal dementia and amyotrophic lateral sclerosis ( Su et al, 2014 ; Simone et al, 2018 ); the CGG repeat (rCGG exp ), which causes fragile X–associated tremor/ataxia syndrome ( Disney et al, 2012 ; Qurashi et al, 2012 ; Yang et al, 2015 ; Green et al, 2019 ); and the CUG repeat r(CUG) exp ( Parkesh et al, 2012 ; Luu et al, 2016 ; Rzuczek et al, 2017 ; Li et al, 2018a ; Angelbello et al, 2019 ), which is associated with myotonic dystrophy type 1. Interestingly, there are several G-quadruplex motifs located on the 5′UTR of oncogenic KRAS transcript that could be targeted by 4,11-bis(2-aminoethylamino)anthra[2,3-b]furan-5,10-dione and 4,11-bis(2-aminoethylamino)anthra[2,3-b]thiophene-5,10-dione for the control of cancer cell proliferation and colony formation ( Miglietta et al, 2017 ).…”
Section: Rnas As Therapeutic Targets For Small Moleculesmentioning
confidence: 99%
“…Some small molecules were also found to act on other types of disease-related RNAs or pathogenic RNA motifs. Many of them are for RNA repeats, such as the expanded GGGGCC repeat [r(GGGGCC) exp , or r(G4C2) exp , or G-quadruplex RNA], which causes frontotemporal dementia and amyotrophic lateral sclerosis ( Su et al, 2014 ; Simone et al, 2018 ); the CGG repeat (rCGG exp ), which causes fragile X–associated tremor/ataxia syndrome ( Disney et al, 2012 ; Qurashi et al, 2012 ; Yang et al, 2015 ; Green et al, 2019 ); and the CUG repeat r(CUG) exp ( Parkesh et al, 2012 ; Luu et al, 2016 ; Rzuczek et al, 2017 ; Li et al, 2018a ; Angelbello et al, 2019 ), which is associated with myotonic dystrophy type 1. Interestingly, there are several G-quadruplex motifs located on the 5′UTR of oncogenic KRAS transcript that could be targeted by 4,11-bis(2-aminoethylamino)anthra[2,3-b]furan-5,10-dione and 4,11-bis(2-aminoethylamino)anthra[2,3-b]thiophene-5,10-dione for the control of cancer cell proliferation and colony formation ( Miglietta et al, 2017 ).…”
Section: Rnas As Therapeutic Targets For Small Moleculesmentioning
confidence: 99%
“…We have reported different types of molecules that bind to r(CUG) repeat and modulate the alternative splicing in DM1 cells [30–33] . After structure–activity studies on small molecules targeting the r(CUG) repeat, we revisited 1,3‐diaminoisoquinoline derivatives with an additional aromatic unit at the C5 position and found a monomeric 1,3‐diaminoisoquinoline ligand JM608 and its dimeric form JM642 .…”
Section: Figurementioning
confidence: 99%
“…We have reported different types of molecules that bind to r(CUG) repeat and modulate the alternative splicing in DM1 cells. [30][31][32][33] After structure-activity studies on small molecules targetingt he r(CUG) repeat, we revisited 1,3-diaminoisoquinoline derivativesw ith an additional aromatic unit at the C5 position and found am onomeric 1,3-diaminoisoquinoline ligand JM608 and its dimericf orm JM642. ( Figure 1) While the detail of structure-activity studies will be reported elsewhere, in brief, the substituent at the C5 position of the 1,3-diaminoisoquinoline chromophore showed as ignificant effect on the binding to the CUG repeatR NA.…”
mentioning
confidence: 99%
“…In vivo activity in a DM1mouse model was also observed even if it is clear that activity and selectivity should be improved in order to reach a satisfying therapeutic effect. 73 Beside DM1 and DM2 trinucleotide repeats, the rCGG repeats involved in fragile X-associated tremor ataxia syndrome (FXTAS) have been explored as targets for small molecules (Fig. 6A).…”
Section: Targeting Of Rna Nucleotide Repeatsmentioning
confidence: 99%